Expression of membrane proteins in the eyes of transgenic Drosophila melanogaster - Hackmann, Yvonne; Jödicke, Lisa; Panneels, Valérie; Sinning, Irmgard (Membrane proteins, 2015)
In recent years, improved protein expression and crystallization strategies, as well as advanced synchrotron radiation sources and crystallographic tools considerably increased the number of crystal structures of integral membrane proteins from higher eukaryotes. However, seen as a proportion of the total number of candidate proteins, these achievements still appear meager, reflecting the huge effort that is often required to obtain high-level and functional expression of eukaryotic membrane proteins. Besides bacteria, yeast, insect, or mammalian cells are frequently used for heterologous expression, but despite considerable investments in time, labor, and money, there are numerous drawbacks to these systems. Are there other strategies that allow for an effective, large-scale production of functional membrane proteins? This chapter describes the expression of proteins in photoreceptor cells of transgenic Drosophila as an easily accessible, versatile alternative. We present step-by-step protocols starting from the cloning of the target gene into a suitable vector for fly eye expression and ending with the harvest of transgenic Drosophila and subsequent protein purification from the eye. Our examples span a number of eukaryotic membrane proteins from different classes—including receptors, transporters, channels, and enzymes—that were successfully expressed without further optimization. The protocols provided here are robust and straightforward to follow even without prior experience in Drosophila work.